2021
DOI: 10.1200/cci.21.00048
|View full text |Cite
|
Sign up to set email alerts
|

Breast Magnetic Resonance Image Analysis for Surgeons Using Virtual Reality: A Comparative Study

Abstract: PURPOSE The treatment of breast cancer, the leading cause of cancer and cancer mortality among women worldwide, is mainly on the basis of surgery. In this study, we describe the use of a medical image visualization tool on the basis of virtual reality (VR), entitled DIVA, in the context of breast cancer tumor localization among surgeons. The aim of this study was to evaluate the speed and accuracy of surgeons using DIVA for medical image analysis of breast magnetic resonance image (MRI) scans relative to stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Many breast cancer survivors experience physical and psychological symptoms (such as pain, fatigue, depression, anxiety, and lymphedema); functional deficits (such as reduced shoulder range of motion and cognitive impairment); emotional problems (such as fatigue, pain, anxiety, and depression); and other complications such as bleeding, effusion, and flap necrosis. Side effects from breast cancer or treatment can have a significant impact on the quality of life (QoL) of breast cancer survivors [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many breast cancer survivors experience physical and psychological symptoms (such as pain, fatigue, depression, anxiety, and lymphedema); functional deficits (such as reduced shoulder range of motion and cognitive impairment); emotional problems (such as fatigue, pain, anxiety, and depression); and other complications such as bleeding, effusion, and flap necrosis. Side effects from breast cancer or treatment can have a significant impact on the quality of life (QoL) of breast cancer survivors [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have shown that 3D-VR improves the speed and accuracy of surgeon analysis, specifically via the accuracy of preoperative MRI scans prior to breast surgical interventions. [2][3][4] Moreover, it has shown a better understanding of the anatomy among different surgical fields such as craniofacial trauma, complex congenital disease surgery, urology, abdominal pediatric surgery, surgical oncology, plastic surgery, among others. [5][6][7][8][9][10] We present the use of 3D-VR in a breast cancer patient who underwent nipple sparing mastectomy (NSM) with reconstruction as an additional tool to improve surgical planning.…”
Section: Introductionmentioning
confidence: 99%
“…Some visualization tools based on VR have been developed and AVATAR medical is one of them. Its usefulness for analysing breast MRI in the context of BC has been recently assessed [6].…”
Section: Introductionmentioning
confidence: 99%